EFFECT OF PARENTS’ INCOME TOWARD STUDENTS’ LEARNING MOTIVATION OF REMPAK, SABAK AUH, SIAK. - Nursila '; Bedriati Ibrahim Bedriati Ibrahim; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Background of this thesis is every human in completing and carrying out their life’s needed dependent by other people. In social life, family is the smallest unit that has big role in continuity of social life . Parents’ income also determine the availability of students’ learning facilities. Learning motivation is the whole of motivator power inside of the students that bring about learning activity, guaranteethe continuity of learning activity, give direction to learning activity for the goals. Motivation can determine good or not in achieving the goals so that more motivation, more succeed. The research aims to find out the parents’ income of students, to find out the students’ learning motivation, to find out the effect of the parents’ income toward students’ learning motivation of Rempak, Sabak Auh, Siak. Qualitative and quantitative descriptive methode were used in this research. Research result showed that the parents’ income has positive effect toward students’ learning motivation. It can be seen from the achievement of all learning motivation’ indicators: strength of willingness to do, time total provided to learning, persistence in doing tasks, tenacity to solving problems (no quick to give up), stable in maintaining opinions, and prefer to work independently.Keywords: Income & Learning Motivation